The Impact of Direct Reservations and OTAs on Grand City Hall Occupancy - Finna Auliya Azzahra Lubis; Cece (CV. Muris Global Education, 2026)
The purpose of this study is to analyze the effect of bookings made through Direct Reservation and Online Travel Agent (OTA) channels on the room occupancy rate. This research adopts a quantitative approach by using internal hotel data recorded on a daily basis over a one-month observation period. The research variables comprise the total number of bookings generated through direct reservations and online travel agents as independent variables, while the room occupancy rate serves as the dependent variable. The data were analyzed using descriptive statistics and multiple linear regression to examine the relationship and the direction of influence among variables. The results indicate a positive effect of bookings from both direct channels and online travel agents on the occupancy rate. Simultaneously, the two booking channels contribute substantially to increasing room occupancy. Partially, the online travel agent channel exerts a more dominant influence in improving occupancy compared to direct reservations. These findings highlight the importance of strategically managing the booking channel mix to maintain occupancy stability and support room sales performance. Therefore, the hotel should optimize the use of online travel agents as a key driver of occupancy volume while strengthening the direct booking channel to foster repeat guests through a positive experience that shapes guests' overall evaluations.